POTENTIAL GENETIC AGENT BFL1 FOR TARGETED THERAPY IN CHRONIC LYMPHOCYTIC LEUKEMIA - Franiak-Pietryga, Ida; Tymoniuk, BogusÅ‚aw; Borowiec, Maciej; Ziolkowska, Ewelina; Blonski, Jerzy Z.; Janus, Agnieszka; Misiewicz, Malgorzata; Wawrzyniak, Ewa; Trelinski, Jacek; Robak, Tadeusz; Maciejewski, Henryk; Tomasiuk, Ryszard; et al. (European Scientific Journal, ESJ, 2015)
Background: Many prognostic factors have been identified in chronic lymphocytic leukemia (CLL) but new ones are still desired. The biological characterization of CLL is now being translated into novel treatment strategies. One new prognostic factor, and therapeutic target, may be BFL1. It is both a serum and a molecular marker that contributes to the progression of CLL and its resistance to chemotherapy. The aim of this study was to evaluate the prognostic value of BFL1 and to assess its correlation with other known prognostic markers in CLL for the cladribine and cyclophosphamide regimen (CC). Methods: qPCR TaqManÂ® Low Density Array was used for gene expression measurements. Assessment of CD38, ZAP70 and BFL-1 proteins expression was done by means of flow cytometry. Serum TK activity was measured by immunoassay. Results: Protein BFL1 expression was found to be significantly higher in CLL patients than healthy volunteers (p=0.001). Moreover its level was significantly higher in patients with no response (NR) to CC therapy (p=0.009). The expression of BFL1 was considerably down regulated during CC treatment and BFL1 mRNA levels were inversely correlated with apoptotic response. In addition, protein BFL1 expression was found to be similar to thymidine kinase (TK) concentration regarding treatment response. As far as other markers are concerned, a positive correlation was identified between BFL1 and TK (r=0.52, p=0.01). Conclusions: Our findings suggest that BFL1 contributes to chemoresistance and may be a co-existing prognostic factor in CLL in the future.